High-corrosion-resistance carbon steel-aluminum composite plate and preparation method thereof

By forming a corrosion-resistant aluminum alloy coating on the carbon steel substrate, using magnesium and aluminum to form a solid solution, combined with alumina powder, epoxy resin and silane coupling agent, laser cladding technology is used to solve the problems of easy corrosion of traditional carbon steel materials and insufficient aluminum strength, and achieve high corrosion resistance and high strength carbon steel-aluminum composite board.

CN119824413AInactive Publication Date: 2025-04-15SHANGHAI SHUNFENG MACHINERY MFG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510322289.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional carbon steel materials are prone to corrosion in harsh environments, while aluminum materials are corrosion-resistant but have low strength, making it difficult to take into account both high strength and high corrosion resistance in industrial applications.

Method used

By forming a corrosion-resistant aluminum alloy coating on the carbon steel substrate, using magnesium and aluminum to form a solid solution, combining alumina powder, epoxy resin and silane coupling agent, and using laser cladding technology to form a dense coating, significantly improving the corrosion resistance and overall performance of the composite panel.

Benefits of technology

It significantly improves the corrosion resistance and overall performance of carbon steel-aluminum composite boards, combines the high strength of carbon steel and the good corrosion resistance of aluminum, extends the service life of the composite boards, and reduces energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a high-corrosion-resistance carbon steel-aluminum composite plate and a preparation method thereof, and belongs to the technical field of metal composite materials. Aluminum and magnesium are combined to form a solid solution structure, so that the strength and corrosion resistance of the aluminum alloy are remarkably improved; and a KCl and LiF mixture is used as a mixed molten salt fluxing agent, so that the smelting temperature is reduced, the melting process is accelerated, uniform distribution of aluminum and magnesium elements is effectively promoted, and the homogeneity and the performance stability of the aluminum alloy are further improved. In order to enhance the performance of the composite board, aluminum oxide is introduced to further improve the hardness and wear resistance of the coating, and the corrosion resistance is additionally provided; epoxy resin is adopted as an adhesive, and a compact and durable corrosion-resistant coating is formed by using excellent adhesion and curing performance of the epoxy resin; and by adding the silane coupling agent, chemical bonds are established among the aluminum oxide powder, the epoxy resin and the aluminum alloy, stable combination among the components is promoted, and the overall structural strength and corrosion resistance of the composite board are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal composite materials and relates to a high-corrosion-resistant carbon steel-aluminum composite plate and a preparation method thereof. Background Art

[0002] With the continuous development of modern industrial technology, the requirements for material performance in the fields of marine engineering, chemical industry, construction, etc. are increasing day by day. Among them, the corrosion resistance of materials in harsh outdoor working environments has become a key indicator. Traditional carbon steel materials have high strength but are prone to corrosion, while aluminum has good corrosion resistance but low strength. Therefore, it is of great significance to develop a composite plate that combines the high strength of carbon steel and the high corrosion resistance of aluminum. This experimental plan aims to propose a new high-corrosion-resistant carbon steel-aluminum composite plate and its innovative preparation method, which significantly improves the comprehensive performance of the composite plate through unique interface bonding technology and surface treatment process. Summary of the invention

[0003] The object of the present invention is to provide a highly corrosion-resistant carbon steel-aluminum composite plate and a preparation method thereof, which has the characteristics of high corrosion resistance.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A highly corrosion-resistant carbon steel-aluminum composite plate comprises a carbon steel substrate and a corrosion-resistant aluminum alloy coating. The corrosion-resistant aluminum alloy coating has the following formula: by weight: 40-50 parts of aluminum powder, 5-15 parts of magnesium powder, 1-3 parts of mixed molten salt, 20-30 parts of alumina powder, 10-15 parts of epoxy resin, 15-20 parts of acetone, and 0.5-2 parts of silane coupling agent. S1-1: According to the formula, aluminum powder, magnesium powder and mixed molten salt are placed in a vacuum melting furnace for melting. The melting temperature is set to 700-800 °C and the melting time is 30 min. After rapid pouring, aluminum alloy is obtained. S1-2: Alumina powder, epoxy resin and acetone were mixed, stirred at 90 °C and 700-800 r / min for 50 min, silane coupling agent was added, stirring was continued for 30 min, and then sprayed on the aluminum alloy surface with a spray gun; S1-3: Using laser to clad the coating on the surface of the aluminum alloy, the laser used is a fiber laser with a laser power of 1500 W to 1800 W to obtain the corrosion-resistant aluminum alloy coating.

[0005] Furthermore, the mixed molten salt is a mixture of KCl and LiF, wherein the mass ratio of KCl to LiF is 2:3.

[0006] Furthermore, the silane coupling agent is one of KH550, KH560 and KH570.

[0007] Furthermore, the epoxy resin in S1-2 is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin.

[0008] Furthermore, the heating rate of the vacuum melting furnace in S1-1 is 5°C / min.

[0009] Furthermore, in S1-2, the spraying distance of the spray gun is 15 cm and the air pressure is 0.5 MPa.

[0010] Furthermore, in the S1-3, the spot diameter is 3 mm and the cladding speed is 200-300 mm / min.

[0011] A method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate, the specific steps of the preparation method are as follows: S8-1: The carbon steel was cleaned with an acetic acid solution and a sodium hydroxide solution respectively, and then washed with deionized water until the pH of the eluent was 7-8, and naturally air-dried at room temperature for 24 h to obtain a carbon steel substrate; S8-2: performing surface treatment on the corrosion-resistant aluminum alloy coating, and grinding the bonding surface between the aluminum alloy coating and the carbon steel substrate with water-abrasive sandpaper to improve the bonding strength with the carbon steel substrate; S8-3: welding the carbon steel substrate and the polished corrosion-resistant aluminum alloy cladding to obtain the highly corrosion-resistant carbon steel-aluminum composite plate.

[0012] Furthermore, the concentration of the acetic acid solution in S8-1 is 2 M, and the concentration of the sodium hydroxide solution is 1 M.

[0013] Furthermore, in S8-2, the bonding surface between the aluminum alloy coating and the carbon steel substrate is polished to a roughness of 0.25-0.35 μm.

[0014] The addition of magnesium will combine with aluminum to form a solid solution. This structural change significantly enhances the overall performance of the aluminum alloy. The formation of the solid solution not only improves the strength of the aluminum alloy, but also optimizes its corrosion resistance. In this process, the mixed molten salt acts as a flux, playing a key role in lowering the smelting temperature and accelerating the melting process; more importantly, the molten salt can also effectively promote the uniform distribution of aluminum and magnesium elements in the melt, thereby further improving the homogeneity and performance stability of the alloy.

[0015] The addition of alumina powder not only significantly improves the hardness and wear resistance of the coating, but also provides additional corrosion resistance, further extending the service life of the composite board. In order to achieve a firm bond between the alumina powder and the surface of the aluminum alloy, epoxy resin is introduced as an adhesive. With its excellent adhesion and curing properties, epoxy resin can ensure that the alumina powder forms a dense and durable coating on the surface of the aluminum alloy. The addition of silane coupling agent plays a bridging role, which can establish a chemical bond between the alumina powder, epoxy resin and the aluminum alloy, thereby significantly improving the adhesion between the three. The formation of this chemical bond not only enhances the firmness of the coating, but also improves the overall structural strength and corrosion resistance of the composite board.

[0016] Alumina and aluminum alloys have significant affinity in composition. Since both contain aluminum, it is easier to achieve metallurgical bonding when alumina powder is laser clad on the surface of aluminum alloy. Laser cladding technology uses high-energy laser beams to quickly melt the coating material and form a metallurgical bond with the aluminum alloy. This bonding method is stronger than traditional mechanical bonding or physical adsorption, and can significantly improve the bonding strength between the coating and the aluminum alloy. Under suitable process conditions, the bonding force between the alumina corrosion-resistant coating and the substrate can reach a very high level, ensuring that the coating is not easy to fall off or peel off during use. At the same time, laser cladding technology is a non-contact processing method that can achieve precise local heating and reduce energy consumption. Compared with traditional methods such as thermal spraying and arc cladding, laser cladding can effectively reduce energy consumption and environmental pollution, and meet the requirements of sustainable development.

[0017] Beneficial effects of the present invention: (1) The addition of magnesium combines with aluminum to form a solid solution, significantly enhancing the overall properties of the aluminum alloy, including strength and corrosion resistance. The mixed molten salt acts as a flux, which effectively reduces the melting temperature, accelerates the melting process, and promotes the uniform distribution of alloying elements in the melt, further improving the homogeneity and performance stability of the alloy.

[0018] (2) The addition of alumina powder significantly improves the hardness and wear resistance of the coating, and further enhances its corrosion resistance, thereby extending the service life of the composite plate. By introducing epoxy resin as a binder and utilizing its excellent adhesion and curing properties, it ensures that the alumina powder forms a dense and durable coating on the surface of the aluminum alloy. In addition, the addition of silane coupling agent establishes a chemical bond between the alumina powder, epoxy resin and aluminum alloy, significantly improving the adhesion between the three, thereby enhancing the firmness of the coating and improving the overall structural strength and corrosion resistance of the composite plate.

[0019] (3) Alumina and aluminum alloys have a strong affinity because they both contain aluminum. Laser cladding technology can quickly achieve metallurgical bonding and greatly improve the bonding strength between the coating and the aluminum alloy, ensuring that the coating is stable and does not fall off. At the same time, this technology is a non-contact processing with precise local heating, which effectively reduces energy consumption and environmental pollution and meets the needs of sustainable development. DETAILED DESCRIPTION

[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0021] The thickness of the carbon steel substrate used in the embodiments and comparative examples is 12 mm, and the specific composition is shown in the following table: Example 1 A highly corrosion-resistant carbon steel-aluminum composite plate comprises a carbon steel substrate and a corrosion-resistant aluminum alloy cladding. The corrosion-resistant aluminum alloy cladding has a formula 1 as follows: by weight: 40 parts of aluminum powder, 5 parts of magnesium powder, 1 part of mixed molten salt, 20 parts of alumina powder, 10 parts of bisphenol A epoxy resin, 15 parts of acetone, and 0.5 parts of silane coupling agent KH550. S1-1: According to formula 1, aluminum powder, magnesium powder and mixed molten salt are put into a vacuum melting furnace for melting. The mixed molten salt is a mixture of KCl and LiF, wherein the mass ratio of KCl to LiF is 2:3. The temperature is set to 700 °C, the heating rate is 5 °C / min, the melting time is 30 min, and the aluminum alloy is obtained after rapid pouring; S1-2: Alumina powder, epoxy resin and acetone were mixed, stirred at 90 °C and 700 r / min for 50 min, silane coupling agent was added, and stirring was continued for 30 min. Then, the mixture was sprayed on the aluminum alloy surface with a spray gun at a spray distance of 15 cm and an air pressure of 0.5 MPa. S1-3: A coating is clad on the surface of the aluminum alloy using a laser. The laser used is a fiber laser with a laser power of 1500 W, a spot diameter of 3 mm, and a cladding speed of 200 mm / min, to obtain the corrosion-resistant aluminum alloy coating with a thickness of 5 mm.

[0022] A method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate, the specific steps of the preparation method are as follows: S8-1: The carbon steel was cleaned with 2 M acetic acid solution and 1 M sodium hydroxide solution, respectively, and then washed with deionized water until the pH of the eluent was 7, and naturally air-dried at room temperature for 24 h to obtain a carbon steel substrate; S8-2: performing surface treatment on the corrosion-resistant aluminum alloy coating, grinding the bonding surface between the aluminum alloy coating and the carbon steel substrate to a roughness of 0.25 μm using 300-grit water-abrasive paper to improve the bonding strength with the carbon steel substrate; S8-3: welding the carbon steel substrate and the polished corrosion-resistant aluminum alloy cladding to obtain the highly corrosion-resistant carbon steel-aluminum composite plate.

[0023] Example 2 A highly corrosion-resistant carbon steel-aluminum composite plate comprises a carbon steel substrate and a corrosion-resistant aluminum alloy cladding. The corrosion-resistant aluminum alloy cladding has a formula 2 as follows: by weight: 45 parts of aluminum powder, 10 parts of magnesium powder, 2 parts of mixed molten salt, 25 parts of alumina powder, 12 parts of bisphenol F epoxy resin, 17 parts of acetone, and 1 part of silane coupling agent KH560. S1-1: According to formula 2, aluminum powder, magnesium powder and mixed molten salt are put into a vacuum melting furnace for melting. The mixed molten salt is a mixture of KCl and LiF, wherein the mass ratio of KCl to LiF is 2:3. The temperature is set to 750 °C, the heating rate is 5 °C / min, the melting time is 30 min, and the aluminum alloy is obtained after rapid pouring; S1-2: Alumina powder, epoxy resin and acetone were mixed, stirred at 90 °C and 750 r / min for 50 min, silane coupling agent was added, and stirring was continued for 30 min. Then, the mixture was sprayed on the aluminum alloy surface with a spray gun at a spray distance of 15 cm and an air pressure of 0.5 MPa. S1-3: A coating is clad on the surface of the aluminum alloy using a laser. The laser used is a fiber laser with a laser power of 1700 W, a spot diameter of 3 mm, and a cladding speed of 250 mm / min, to obtain the corrosion-resistant aluminum alloy coating with a thickness of 5 mm.

[0024] A method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate, the specific steps of the preparation method are as follows: S8-1: The carbon steel was cleaned with 2 M acetic acid solution and 1 M sodium hydroxide solution, respectively, and then washed with deionized water until the pH of the eluent was 7.5, and naturally air-dried at room temperature for 24 h to obtain a carbon steel substrate; S8-2: performing surface treatment on the corrosion-resistant aluminum alloy coating, grinding the bonding surface between the aluminum alloy coating and the carbon steel substrate to a roughness of 0.3 μm using 300-grit water-abrasive paper to improve the bonding strength with the carbon steel substrate; S8-3: welding the carbon steel substrate and the polished corrosion-resistant aluminum alloy cladding to obtain the highly corrosion-resistant carbon steel-aluminum composite plate.

[0025] Example 3 A highly corrosion-resistant carbon steel-aluminum composite plate comprises a carbon steel substrate and a corrosion-resistant aluminum alloy cladding. The corrosion-resistant aluminum alloy cladding has a formula 3 as follows: by weight: 50 parts of aluminum powder, 15 parts of magnesium powder, 3 parts of mixed molten salt, 30 parts of alumina powder, 15 parts of bisphenol S epoxy resin, 20 parts of acetone, and 2 parts of silane coupling agent KH570. S1-1: According to formula 3, aluminum powder, magnesium powder and mixed molten salt are put into a vacuum melting furnace for melting. The mixed molten salt is a mixture of KCl and LiF, wherein the mass ratio of KCl to LiF is 2:3. The temperature is set to 800 °C, the heating rate is 5 °C / min, the melting time is 30 min, and the aluminum alloy is obtained after rapid pouring; S1-2: Alumina powder, epoxy resin and acetone were mixed, stirred at 90 °C and 800 r / min for 50 min, silane coupling agent was added, and stirring was continued for 30 min. Then, the mixture was sprayed on the aluminum alloy surface with a spray gun at a spray distance of 15 cm and an air pressure of 0.5 MPa. S1-3: A coating is clad on the surface of the aluminum alloy using a laser. The laser used is a fiber laser with a laser power of 1800 W, a spot diameter of 3 mm, and a cladding speed of 300 mm / min, to obtain the corrosion-resistant aluminum alloy coating with a thickness of 5 mm.

[0026] A method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate, the specific steps of the preparation method are as follows: S8-1: The carbon steel was cleaned with 2 M acetic acid solution and 1 M sodium hydroxide solution, respectively, and then washed with deionized water until the pH of the eluent was 8, and naturally air-dried at room temperature for 24 h to obtain a carbon steel substrate; S8-2: performing surface treatment on the corrosion-resistant aluminum alloy coating, grinding the bonding surface between the aluminum alloy coating and the carbon steel substrate to a roughness of 0.35 μm using 300-grit water-abrasive paper to improve the bonding strength with the carbon steel substrate; S8-3: welding the carbon steel substrate and the polished corrosion-resistant aluminum alloy cladding to obtain the highly corrosion-resistant carbon steel-aluminum composite plate.

[0027] Comparative Example 1 No magnesium powder was added, and the remaining steps were the same as those in Example 1.

[0028] Comparative Example 2 No alumina ceramic powder was added, and the remaining steps were the same as those in Example 1.

[0029] Comparative Example 3 No silane coupling agent was added, and the remaining steps were consistent with those in Example 1.

[0030] Comparative Example 4 The laser cladding step is not performed, and the remaining steps are consistent with Example 1.

[0031] The corrosion resistance test of the embodiments and comparative examples was carried out according to GB1771-91. The test temperature was 40°C, the spray medium was 5% sodium chloride solution, and the salt spray was carried out for 15 minutes every 45 minutes.

[0032] The experimental results are summarized in the following table: It can be seen from the examples and comparative data that forming an alloy solid solution using magnesium and aluminum, introducing alumina ceramic powder, epoxy resin and silane coupling agent, and adding a corrosion-resistant coating on the surface of the aluminum alloy using laser cladding technology is beneficial to further increase its corrosion resistance.

[0033] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A highly corrosion-resistant carbon steel-aluminum composite plate, characterized in that: It comprises a carbon steel substrate and a corrosion-resistant aluminum alloy coating. The corrosion-resistant aluminum alloy coating has the following formula: by weight, 40-50 parts of aluminum powder, 5-15 parts of magnesium powder, 1-3 parts of mixed molten salt, 20-30 parts of alumina powder, 10-15 parts of epoxy resin, 15-20 parts of acetone, and 0.5-2 parts of silane coupling agent. S1-1: According to the formula, aluminum powder, magnesium powder and mixed molten salt are placed in a vacuum melting furnace for melting. The melting temperature is set to 700-800 °C and the melting time is 30 min. After rapid pouring, aluminum alloy is obtained. S1-2: Alumina powder, epoxy resin and acetone were mixed, stirred at 90 °C and 700-800 r / min for 50 min, silane coupling agent was added, stirring was continued for 30 min, and then sprayed on the aluminum alloy surface with a spray gun; S1-3: Using laser to clad the coating on the surface of the aluminum alloy, the laser used is a fiber laser with a laser power of 1500W~1800W to obtain the corrosion-resistant aluminum alloy coating.

2. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: The mixed molten salt is a mixture of KCl and LiF, wherein the mass ratio of KCl to LiF is 2:

3.

3. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: The silane coupling agent is one of KH550, KH560 and KH570.

4. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: The epoxy resin in S1-2 is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin.

5. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: The heating rate of the vacuum melting furnace in S1-1 is 5°C / min.

6. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: The spraying distance of the spray gun in S1-2 is 15 cm and the air pressure is 0.5 MPa.

7. The highly corrosion-resistant carbon steel-aluminum composite plate according to claim 1, characterized in that: In the S1-3, the spot diameter is 3 mm and the cladding speed is 200-300 mm / min.

8. A method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate according to any one of claims 1 to 7, characterized in that: The specific steps of the preparation method are as follows: S8-1: The carbon steel was cleaned with an acetic acid solution and a sodium hydroxide solution respectively, and then washed with deionized water until the pH of the eluent was 7-8, and naturally air-dried at room temperature for 24 h to obtain a carbon steel substrate; S8-2: performing surface treatment on the corrosion-resistant aluminum alloy coating, and grinding the bonding surface between the aluminum alloy coating and the carbon steel substrate with water-abrasive sandpaper to improve the bonding strength with the carbon steel substrate; S8-3: welding the carbon steel substrate and the polished corrosion-resistant aluminum alloy cladding to obtain the highly corrosion-resistant carbon steel-aluminum composite plate.

9. The method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate according to claim 8, characterized in that: The concentration of the acetic acid solution in S8-1 is 2 M, and the concentration of the sodium hydroxide solution is 1 M.

10. The method for preparing a highly corrosion-resistant carbon steel-aluminum composite plate according to claim 8, characterized in that: In the S8-2, the bonding surface between the aluminum alloy cladding and the carbon steel substrate is polished to a roughness of 0.25-0.35 μm.

Citation Information

Patent Citations

  • Method for synthetizing nanometer alumina reinforced laser clad layer in advance on aluminium alloy surface

    CN101812685A

  • Modified alumina composite material, copper-coated substrate and preparation method of copper-coated substrate

    CN104371274A

  • Surface working method and surface working device

    JP1995228980A

  • Method for joining different material

    JP2012135811A